Pharmacokinetics of Dermatan Sulfate in the Rabbit After Intravenous Injection - Dol, F; Houin, G; Dupouy, D; Cadroy, Y; Caranobe, C; Gabaig, A M; Mardiguian, J; Sie, P; Boneu, B (Thrombosis and Haemostasis, 1988)
To investigate the pharmacokinetic properties of dermatan sulfate (DS), a new potential antithrombotic agent, two different approaches were used. In the first one, DS was derivatized with 3-4 hydroxyphenyl propionic acid N hydroxysuccinimide ester (SHPP) and iodinated. The labelled derivative was injected by IV route to rabbits with increasing doses of unlabelled compound ranging from 20 to 4000 μg/kg. The disappearance of DS from plasma was characterized by measuring both the circulating radioactivity and the biological activity using an original assay based upon the catalysis of heparin cofactor II – thrombin formation. The radioactivity data indicated that the volume of distribution, the clearance and the half life of the tracer were independent of the dose of DS injected. DS concentrations measured by the bioassay indicated that more than 90% were cleared with half lives close to those calculated from the radioactivity data; the remaining biological activity was cleared at a slower rate. Experiments performed with bi-nephrectomized animals indicated that the kidneys play a major role in the elimination of DS or of its metabolites which may have a residual biological activity. In the second set of experiments, unlabelled DS was delivered under continuous intravenous infusion for 5 hours at 5 increasing doses ranging from 160 to 4200 μg/kg/h. The biological activities were used to measure the plateau concentration of DS: there was a linear relationship between the dose delivered and the plasma concentration. These data indicate that the pharmacokinetic profile of DS is very close to that of low molecular weight heparin, and quite different from that of SH.
Keywords: Dermatan sulfate; Pharmacokinetics